2018
DOI: 10.5812/semj.62299
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Hospital Nurses’ Moral Intelligence: A Cross-Sectional Study in Guilan Province, North of Iran

Abstract: Background: The emphasis placed on ethics and moral considerations has always been considered in individual and social domains, and moral intelligence is one of the important components that can play a key role in the improvement of nursing profession. In fact, among different professions, nursing is a clear indication of moral performance. Objectives: The overriding aim of the present study was to evaluate the moral intelligence of nurses working in hospitals of Guilan Province, Iran. Methods: This cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…At the same time, nurses are thought to have a positive feeling of dedication to care, are optimistic and always ready, are skilled, informed, and resourceful, have respect for the people they care for, and are patient and understanding of their surroundings. In the literature, the levels of moral intelligence of nurses (Dehghani et al, 2020;Majidi et al, 2018) Oluma & Abadiga, 2020) supports our study.…”
Section: Assigned Unitsupporting
confidence: 88%
“…At the same time, nurses are thought to have a positive feeling of dedication to care, are optimistic and always ready, are skilled, informed, and resourceful, have respect for the people they care for, and are patient and understanding of their surroundings. In the literature, the levels of moral intelligence of nurses (Dehghani et al, 2020;Majidi et al, 2018) Oluma & Abadiga, 2020) supports our study.…”
Section: Assigned Unitsupporting
confidence: 88%
“…This questionnaire was validated by Majidi et al in Iran. Its Cronbach's alpha coefficient is reported to be 0.88 [22].…”
Section: Moral Intelligence Questionnairementioning
confidence: 99%
“…The final score ranges between 20 and 100 [ 51 ]. In Iran, Majidi et al (2018) approved the reliability of this questionnaire with Cronbach’s alpha coefficient of 0.88 [ 52 ]. In the present study, ten experts confirmed the face and content validity of the questionnaire.…”
Section: Methodsmentioning
confidence: 99%